HPV Vaccination for Males: A New Perspective on Head and Neck Cancer? Vacina do HPV no Sexo Masculino: Uma Nova Perspetiva no Cancro da Cabeça e Pescoço? - Pinto, Isabel; Almeida, Mário Giesteira; Oliveira, Pedro; Helena, Diamantino; Condé, Artur; Machado, João Firmino (Gazeta Médica, 2019)
Infection by human papillomavirus (HPV) is a necessary cause of cervical cancer, although it is also a risk factor for neoplasms on other areas, namely, head and neck. The increasing incidence of tumors in this region highlights the importance of implementing prevention and control interventions. Considering the effectiveness of HPV vaccine in the reduction of cervical cancer cases it may play a role as a preventive strategy for HPV positive head and neck cancers.